Peranan School Well-Being dan Optimisme Terhadap Flow Akademik pada Mahasiswa Fakultas Psikologi Universitas “X” Padang - Ifani Candra; Hidayah, Nurul (Psyche 165 Journal, 2023)
Being a student faces a lot of problems, both from the surrounding environment and academic problems. This study aims to determine the role of school well-being and optimism in the academic flow of students at the Faculty of Psychology, University "X" in the city of Padang. This study uses a quantitative research approach with survey methods with multiple linear regression analysis techniques. The population in this study were all Psychology students at "X" University in the city of Padang, totaling 803 people and the research sample used a probability sampling technique with a cluster random sampling technique with a significance level of 5% so that the sample in this study was 258 students. The measurement tool for this study uses three scales, namely the Academic Flow scale, the School Well-Being scale and the Optimism scale. Hypothesis testing in this study used multiple linear regression analysis techniques with the help of IBM SPSS 26,0. The results of the analysis show a value of p=0,000 (p<0,01), which indicates that school well-being and optimism can play a very significant role in academic flow. The first minor hypothesis test has a significance value of 0,000 <0,01, which means that school well-being plays a positive and very significant role on academic flow. The results of the second minor hypothesis test have a significance value of 0,000<0.01, meaning that optimism plays a positive and very significant role in academic flow. These findings indicate that when students' school well-being is in good condition, the level of academic flow they have will also be good. Likewise, if students have good optimism from within themselves, this will contribute to a good level of academic flow as well. The effective balance of the two independent variables to the dependent variable is 39,8%.